PELESTARIAN ARSITEKTUR MUSEUM SONOBUDOYO YOGYAKARTA - Titi Handayani (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2017)
Title: Architectural Conservation of Sonobudoyo Museum, Yogyakarta Sonobudoyo Museum has been experiencing many changes. More activities and collections have caused to the increasing number of rooms and new buildings. The problem is that the new building design is not suitable with the original building design and lay out by the Dutch architect, Thomas Karsten. It leads to the decreasing of the quality of the environment, even decreasing the cultural values of the museum as a heritage building. The aim of the research is to study the existing condition of Sonobudoyo Museum in order to understand changes of the original design. Evaluation of all buildings in Sonobudoyo Museum focused on their functions. Method used in this study is descriptive-qualitative. Data and findings of field surveys were analyzed in order to find the architectural characteristics of the museum and its changes. There are four conservation actions to be recommended, which are (1) preservation of buildings as their original design, (2) repairation and restoration buildings, (3) demolition of unapropriate buildings, and (4) location of new buildings.